PERAN PEREMPUAN DALAM KONSERVASI AIR RUMAH TANGGA - Rohendi, Aulia; Nur, Chairan M. (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2018)
The availability of world freshwater that can be used by humans is very small in number compared with many people's estimates, especially for those living in regions with abundant of water. Water conservation should be done according to Islamic advice, then considering other users' water needs, maintaining water quality, saving energy, and considering increasing water demand as per population growth. Prior to the scarcity and water damage, water conservation needs to be done in non-domestic and domestic / household levels. Household water conservation can be done through behavioural change and technological change. This study focuses on changes in household behavior in water conservation related to the role of women. A qualitative approach is applied in this study by conducting interviews with resource persons who play a significant role in environmental issues and some are housewives. The results show that household water conservation can be done in simple and easy ways, for example by monitoring water use by children, choosing water-saving ways of gardening, washing clothes at once, and so on. The role of women in household water conservation is significant because women are the main users of water and women can educate children early on. The government is expected to arrange strategies to promote water conservation on a household scale by educating and disseminating it to women's associations at the village level.Keywords :